THE FEAR OF COVID – 19 AMONG HEALTH CARE PROFESSIONALS – A CROSS SECTION STUDY - PEVEC, TEODOR optional (Medicinski časopis, 2024)
INTRODUCTION: Working conditions for health professionals can be affected greatly by pandemic caused by COVID-19. The aims of the study were to identify the level of fear of COVID-19 in hospital staff.METHODS: This study was carried out in a convenience sample of nurses and medical doctors from four public regional Hospital in Slovenia. This was a cross-sectional survey study in which was used a Fear of COVID-19 Scale. The questionnaire was completed by 110 participants. RESULTS: The sample mean score was 16.3±6.1. More than half of the study participants (61%) considered it as low levels of fear, and 39% the participants considered it as high levels of fear. Employees with less than 27 weeks experience with COVID-19 had a higher mean FCV-19S score (17.6±6.3) than employees with more than 27 weeks of COVID-19 experience (14.7±5.4) and we found a significant difference of p=0.006. Statistically significant differences were found also again between employees’ regarding COVID units (Intensive Care Unit-ICU and Acute Unit-AU; item »afraid of losing life«).CONCLUSIONS: Regardless of the duration of the epidemic, fear is still present. Experience reduces fear among employees.KEY WORDS: COVID 19-9, fear, health professionals
Keywords: COVID 19-9, fear, health professionals